2012
DOI: 10.1074/jbc.m112.385609
|View full text |Cite
|
Sign up to set email alerts
|

Structure, Sulfatide Binding Properties, and Inhibition of Platelet Aggregation by a Disabled-2 Protein-derived Peptide

Abstract: Background: Binding of Dab2 to sulfatides results in platelet aggregation inhibition. Results: The structure of a Dab2-derived peptide (SBM) embedded in dodecylphosphocholine micelles, characterization of its minimal functional sulfatide-binding site, and its inhibitory platelet aggregation activity were determined. Conclusion: An amphipathic helical region of Dab2 SBM binds sulfatides, leading to platelet aggregation inhibition. Significance: Dab2 SBM may lead to the design of novel aggregatory inhibitors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
37
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(47 citation statements)
references
References 60 publications
10
37
0
Order By: Relevance
“…As a promising therapeutic peptide (Fig. ), Dab2 SBM exhibits an anti‐aggregatory platelet activity comparable with that described for Arg‐Gly‐Asp‐Ser (RGDS), a fibrinogen‐derived peptide .…”
Section: Introductionmentioning
confidence: 69%
“…As a promising therapeutic peptide (Fig. ), Dab2 SBM exhibits an anti‐aggregatory platelet activity comparable with that described for Arg‐Gly‐Asp‐Ser (RGDS), a fibrinogen‐derived peptide .…”
Section: Introductionmentioning
confidence: 69%
“…A recent report indicated that sulfatide-laminin binding can initiate basement membrane assembly and signaling ( 9 ). Sulfatide expressed on cell surface exerts biological functions through mediating interactions with various proteins, such as laminin, hepatocyte growth factor, and disabled-2 ( 34 ). Furthermore, the expression and distribution of sulfatide are often altered during development and oncogenic transformation ( 35 ).…”
Section: Discussionmentioning
confidence: 99%
“…Disabled-2 (Dab2) is an adaptor protein expressed in various cell types, including megakaryocytes and platelets [10][11][12]. Dab2 regulates receptor-mediated endocytosis, embryonic development, differentiation, signal transduction, the immune response and platelet activation through interactions with a variety of molecules [10,[12][13][14][15][16][17][18][19][20][21][22][23][24][25]. Dab2 has at least two alternative splicing isoforms (p82 and p59) [26,27].…”
Section: Introductionmentioning
confidence: 99%